IN UTERO HAEMATOPOIETIC STEM CELL TRANSPLANTATION (IUHSCT) - Maria Concetta Renda; Aurelio Maggio (Mediterranean Journal of Hematology and Infectious Diseases)
In utero haematopoietic stem cell transplantation (IUHSCT) is a non-myeloablative approach for the prenatal treatment of genetic disorders. However, in target disorders, where there is not a selective advantage for donor cells, a useful donor-cell  chimerism  has not been achieved There are three  possible  barriers  to engraftment following IUHSCT :  limited space in the fetus due to host-cell competition; the large number of donor cells needed, and the immunological asset of recipient . Animal models have shown different levels of resistance to IUHSCT engraftment.  In primate, goat, rat and mouse  the levels of engraftment that has been achieved were low and not  therapeutic. Among 46 cases of  IUHSCT reported in humans, successful engraftment  was obtained only in cases of  X-SCID. Useful levels of chimerism has not been achieved in non-immunodeficiency diseases, and  a detectable engrafment , was  reported only in one case  of  ß-thalassemia transplanted at 12 weeks of gestation  by fetal liver cells In one a-thalassemia case, where a-globin-dependent hemoglobin production and anemia are present during fetal period, microchimerism  and tolerance were suggested . To overcome the IUHSCT engraftment barriers , it is necessary to develop strategies to improve the competitive capacity of donor cells and  to define the gestational age of the possible immunological “window of opportunity” in the human fetus. In utero haematopoietic stem cell transplantation (IUHSCT) is a non-myeloablative promising approach for the prenatal treatment of a variety of genetic disorders and  could be an alternative  option to therapeutical abortion in some congenital diseases like haematological hereditary  syndromes.